If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = j + -7 Reorder the terms: 9 = -7 + j Solving 9 = -7 + j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-1j' to each side of the equation. 9 + -1j = -7 + j + -1j Combine like terms: j + -1j = 0 9 + -1j = -7 + 0 9 + -1j = -7 Add '-9' to each side of the equation. 9 + -9 + -1j = -7 + -9 Combine like terms: 9 + -9 = 0 0 + -1j = -7 + -9 -1j = -7 + -9 Combine like terms: -7 + -9 = -16 -1j = -16 Divide each side by '-1'. j = 16 Simplifying j = 16
| 3.25x+28.5=48 | | 34-12x=28x-36 | | 5q-4=36 | | x/15=24/9 | | F(6)=3x^2-5x+8 | | 4x^3-20x^2+25x-3=0 | | 34-12x=28x-26 | | 15a^2+3a= | | 2x+9=28-6x | | 5a-3a+7a*4=72 | | 7x+24=12x-12 | | 11+6x=12x-3 | | 8(2x-7)/5=3 | | 9x+12=6x+14 | | -5x+13+6x=2+x+11 | | y-10=1/2x-7/2 | | -10+5(2r-10)=90 | | -4y+7(y+2)=-4 | | 16x+3=6x+24 | | 4a^2+4a^2= | | 5[(2k+1)-3(k-3)]=2(k-10)+7 | | b^2-3b-70=70 | | (3x^2y^-3)^3/27(xy)^-9 | | 6(m+2.6)=56.4 | | 3x+x+4=18 | | x+4=13-x | | 16+a=15 | | 3x+1=7x-17 | | 9x+10=7x+39 | | 4x-2(x+8)=2x+3(4-x) | | 2.7x+4=-5.4x-4.1 | | 2a+a+a=18 |